2019
DOI: 10.1158/1078-0432.ccr-18-2293
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Genotyping of Hepatocellular Carcinoma: Clinical Implications of Next-Generation Sequencing for Matching Patients to Targeted and Immune Therapies

Abstract: Purpose: Prior molecular profiling of hepatocellular carcinoma (HCC) has identified actionable findings that may have a role in guiding therapeutic decision-making and clinical trial enrollment. We implemented prospective next-generation sequencing (NGS) in the clinic to determine whether such analyses provide predictive and/or prognostic information for HCC patients treated with contemporary systemic therapies. Experimental Design: Matched tumor/normal DNA from patients with HCC (N ¼ 127) were analyzed using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
413
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 450 publications
(471 citation statements)
references
References 55 publications
17
413
1
1
Order By: Relevance
“…Among these identified highly mutated genes, TP53, TERT, PEEX2, CTNNB1, and AXIN1 in HCC, especially in HBV‐related HCC, have been investigated, and the published studies showed that these mutated genes played very important roles in the development of HCC . In addition, consistent with the published studies, we found that COL11A1, RB1, MUC16, and PCLO, which have been detected by next‐generation sequencing technology, including whole genome sequencing and whole‐exome sequencing by different groups, are also found to be associated with HCC in our research. However, the role of other mutated genes, including ABCA13, COL11A1, and COL12A1 as shown in Figure A, in HBV‐related HCC, has not been well clarified and needs to be investigated in future studies.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Among these identified highly mutated genes, TP53, TERT, PEEX2, CTNNB1, and AXIN1 in HCC, especially in HBV‐related HCC, have been investigated, and the published studies showed that these mutated genes played very important roles in the development of HCC . In addition, consistent with the published studies, we found that COL11A1, RB1, MUC16, and PCLO, which have been detected by next‐generation sequencing technology, including whole genome sequencing and whole‐exome sequencing by different groups, are also found to be associated with HCC in our research. However, the role of other mutated genes, including ABCA13, COL11A1, and COL12A1 as shown in Figure A, in HBV‐related HCC, has not been well clarified and needs to be investigated in future studies.…”
Section: Discussionsupporting
confidence: 84%
“…Accumulation of genetic alterations is a hallmark of HCC, and a great number of mutated genes, including CTNNB1, TSC1/2, PREX2, TP53, TERT, AXIN1, ARID1A, RET, and ARID2, have been identified in HCC, especially, in HBV‐related HCC . Current studies suggest that the mutations of CTNNB1 are associated with low stage HCC .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This subclass has not been found to influence prognosis. However, molecular profiling of tumour biopsies from advanced HCC has suggested an altered response to immune checkpoint inhibitors . This could be important for future adjuvant/neoadjuvant strategies (see below).…”
Section: Refinement Of Prognosis According To Pathological and Molecumentioning
confidence: 99%